2019
DOI: 10.1093/ejcts/ezz071
|View full text |Cite
|
Sign up to set email alerts
|

Extended-arch repair for acute type-A aortic dissection: perioperative and mid-term results

Abstract: OBJECTIVES: Extended-arch techniques offer the potential to comprehensively treat acute type-A aortic dissection (ATAAD), but add surgical complexity compared to the standard hemiarch technique. This study describes both perioperative and mid-term outcomes following the introduction of an extended-arch technique for ATAAD. METHODS: Ours is a retrospective single-centre observational study of 95 consecutive patients with ATAAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…20 Collectively, findings from our series demonstrate that(1) metrics like NIHSS and mRS, can serve as meaningful surrogates of clinical outcomes after dissection repair that should be reported and that (2) neurologists provide tangible expertise in the diagnosis and management of stroke.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…20 Collectively, findings from our series demonstrate that(1) metrics like NIHSS and mRS, can serve as meaningful surrogates of clinical outcomes after dissection repair that should be reported and that (2) neurologists provide tangible expertise in the diagnosis and management of stroke.…”
mentioning
confidence: 71%
“…Both repair strategies have been previously described and reflect current practice pattern variations in ATAAD. 19,20 Neuroprotective strategy was left to the operating surgeon and generally involved either DHCA to 18°C or selective antegrade cerebral perfusion (SACP), defined as less than two inflow lines to the brain at 20-25°C. De-airing techniques commonly consisted of postural changes, inflation of the lung, air removal via an LV or root vent, and/or direct aspiration of air.…”
Section: Management Of Strokementioning
confidence: 99%
“…Residual patent false lumen is a well-known risk factor for progressive aortic dilatation and poor long-term outcomes following type A AAD surgery [ 16 , 23 , 24 ]. Fichadiya A and his colleagues [ 25 ] analyzed that false lumen thrombosis was achieved in 57 and 9% of patients undergoing extended-arch (total arch) and hemi-arch repair, respectively. Rate of growth in the proximal descending aorta was 0.7 ± 2.3 mm/year in the extended-arch group versus 2.7 ± 3.9 mm/year in the hemi-arch group.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis involving 9 studies and 1827 patients, Yan and colleagues 28 demonstrated that despite significantly lower early mortality with the hemiarch approach (pooled risk ratio 0.71, 95% confidence interval: 0.54-0.94, p ¼ 0.02), it related to significantly higher incidences of aortic reoperation and dilatation of the false lumen (pooled risk ratio 3.14, 95% confidence interval: 1.74 -5.67, p < 0.001), indicating that such an approach carries a 214% increase in risk of aortic events compared to total arch replacement. A 2019 study by Fichadiya and colleagues 29 further supported this by reporting that 22% (13/60) of their hemiarch patients, but none of the extended arch patients (0/28), required open aortic reoperation; in 85% (11/13), it was due to dilatation of the distal arch or proximal descending thoracic aorta. These findings altogether reflect the risk of the hemiarch approach in retaining an incompletely thrombosed or patent false lumen, causing susceptibility to continuous dilatation of the residual aorta upon pressurization, the risk of aortic aneurysms, and the subsequent need for aortic reinterventions.…”
Section: Extent Of Surgical Interventionmentioning
confidence: 93%
“…No differences in outcomes whether aggressive approach pursued or not 1 had no arch procedure More extensive procedure better for younger and hemodynamically stable patients. Fichadiya 29 Study period: 2011-2016 Significantly lower early mortality risk in hemiarch group (pooled risk ratio 0.69, p ¼ 0.005). 95 consecutive ATAAD patients: Significantly higher incidence of postoperative aortic events, including aortic reoperation and significant false lumen dilatation (risk ratio 3.14, p < 0.001).…”
Section: Management Of Cerebral Malperfusionmentioning
confidence: 99%